Indicadores antropométricos de la niñez en situación de calle en Medellín, Colombia (2015)
ABSTRACT: To describe the anthropometric indicators of body mass index for age (BMI/A) and height for age (H/A) in children and adolescents living on the streets of Medellin, according to sociodemographic and drug abuse characteristics. Methodology: a descriptive study of 453 medical and nutritional records of homeless children and adolescents. The anthropometric indicators were categorized according to growth patterns accepted for Colombia. A bivariate descriptive analysis between anthropometric, sociodemographic and drug abuse variables was conducted. Results: 27.8% of children and adolescents had stunting and 35.3%, had risk of stunting. Stunting was higher for men (89.7%) than for women (10.3%) (p <0.05). As for bmi/a, 4.2% of the individuals had thinness, 14.1% risk of thinness and 2.2% had weight excess. Additionally, a statistically significant association (p <0.01) between bmi/a and age and between H/A and sex and educational level was found. Conclusions: the homeless children and adolescents assessed in this study had anthropometric indicators that show an unfavorable nutritional status, especially male adolescents. Besides having programs and policies for recovering this population's nutrition, it is also necessary to prevent the situation of street life in nna, by addressing structural determinants that cause poverty, inequity and food insecurity in the city.